Technology assisted language intervention (TALI) for children who are deaf/hard of hearing: promising impact on pragmatic skills. (2nd October 2022) - Mood, Deborah; Sheldon, Rose; Tabangin, Meredith; Wiley, Susan; Meinzen-Derr, Jareen
ABSTRACT: Children who are deaf and hard of hearing (DHH) often demonstrate pragmatic language difficulties which can impact academic and social outcomes. This randomized control trial for DHH children, ages 3–12 years, explored the Technology-Assisted Language Intervention (TALI), incorporating augmentative and alternative communication technology (AAC) into traditional speech/language therapy, compared to treatment-as-usual (TAU) to determine impact on pragmatics. Pragmatic outcome measures included parent reported Pragmatics Profile of the CELF-5 (for children age ≥5 years) and CELF-P Descriptive Pragmatics Profile (for children <5 years) in addition to parent reported Social and Communication domains of the Vineland Adaptive Behavior Scales, Third Edition (VABS). Over 24 weeks, children ≥5 years in the TALI made significantly more progress (increase in raw scores) on the Pragmatics Profile compared to children in TAU (12.7 points vs. −6.0 points; p = 0.04) and also showed significant gains on two of the three subscales. For children ≥5 years, no significant VABS changes were seen in either intervention group. For children <5 years, there were no statistically significant differences in growth on the CELF-P total pragmatics raw score or on any subdomain. However, children in TALI had significant increases in the mean VABS Communication (86.7–99.1) and Social domain standard scores (91.8–97.4; p = 0.01), while gains for children in TAU on the Communication and Social domain standard scores were not statistically significant. These promising results support the need for additional research exploring the effectiveness of AAC supported speech/language therapy to enhance DHH children's pragmatic language skills. Trial registration: ClinicalTrials.gov identifier: NCT02998164 .